Association of recombinant cotton leaf curl begomovirus with higher Cotton leaf curl disease incidence in Delhi - Khare, V K (Indian Journal of Plant Protection, 2018)
A recent survey of cotton leaf curl disease (CLCuD) in Indian Agricultural Research Institute (IARI), New Delhi cotton felds revealed higher CLCuD incidence of 60.0-70.2% in the year 2015 and 26.9-97.1% in the year 2016. Seven CLCuD-begomovirus isolates collected from infected felds were characterized based on sequence analysis of coat protein (CP) gene. The present isolates showed 94-100% nucleotide identity among them. The phylogenetic analysis determined that fve isolates are members of Cotton leaf curl Multan virus (CLCuMuV)-Rajasthan and two are of Cotton leaf curl Kokran virus (CLCuKoV)-Burewala. Recombination analysis among CP gene of overall 18 CLCuD begomovirus isolates of IARI cotton felds including the seven present and 11 previously reported isolates was conducted. Of them, 14 CLCuMuV-Rajasthan isolates, both the present and previously reported, were detected as recombinants showing break point at 192-584nt (P= 1.197 x 10-3-7.241 x 10-4) of the CP gene. Of the CLCuKoV-Burewala isolates, the present two isolates showed recombination at 629-740nt (P = 1.197 × 10-3) but the previously reported two isolates were non-recombinants. This is the frst report of appearance of recombinant CLCuKoV-Burewala isolate in Delhi. Although most of the CLCuD-begomoviruses in Delhi are recombinant, but the occurrence of higher CLCuD incidence at present condition might be due to appearance of recombinant CLCuKoV isolates.